2020
DOI: 10.1177/1753193420952010
|View full text |Cite
|
Sign up to set email alerts
|

Pain during physical examination of a healing upper extremity fracture

Abstract: The evidence that symptom intensity and magnitude of limitations correlate with thoughts and emotions means that subjective signs, such as pain with physical examination, reflect both physical and mental health. During a 1-month evaluation of a rapidly healing upper extremity fracture with no risk of nonunion, 117 people completed measures of adaptiveness to pain and pain during the physical examination. Greater pain during examination correlated with less adaptive responses to pain and older age. This finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The decision to continue immobilization is often based on radiographs and fracture tenderness. This conflicts with evidence that radiographs are unreliable to diagnose scaphoid union [ 10 12 ] and that pain intensity is strongly correlated to coping strategies in response to nociception in patients with upper extremity injury [ 14 17 ]. The discrepancy between current evidence and surgeon-decision making may result in unhelpful additional immobilization.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The decision to continue immobilization is often based on radiographs and fracture tenderness. This conflicts with evidence that radiographs are unreliable to diagnose scaphoid union [ 10 12 ] and that pain intensity is strongly correlated to coping strategies in response to nociception in patients with upper extremity injury [ 14 17 ]. The discrepancy between current evidence and surgeon-decision making may result in unhelpful additional immobilization.…”
Section: Discussionmentioning
confidence: 94%
“…There is considerable evidence that pain intensity is strongly associated with symptoms of depression, anxiety and less effective coping strategies in response to nociception [15][16][17]. Gonzalez et al [14] reported a correlation between greater pain on examination and less adaptive responses to pain among 117 people with a healing upper extremity function with no risk of nonunion. This suggests that fracture tenderness may not be a helpful measure of fracture union.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that diagnosing mild-to-moderate IMNCT using signs and symptoms alone may be discordant from diagnosis using EDS and US measurements indicates the need for a better diagnostic strategy or tool for mild-to-moderate IMNCT. Given that unhelpful thoughts (interpretations) and distress (worry or despair) can alter symptoms [1, 3, 6-8, 17, 18, 20], and might alter clinician interpretation via stress contagion (where the clinician adopts the unsettlement of the patient [11]), it might be helpful for a new tool to account for mindset and circumstances. A diagnostic tool for mild-to-moderate IMNCT might benefit from other items, such as relief of paresthesia using night splinting, which was considered but did not add additional information in the development of the CTS-6 in patients with severe IMNCT [10].…”
Section: Discussionmentioning
confidence: 99%
“…Our classes might not align precisely with our common understanding of median neuropathy (IMNCT) and its characteristic symptoms and signs (CTS). However, the identified classes resemble clinical practice, where surgery might have more potential for benefit than for harm in patients with mild-to-moderate IMNCT, but not in those with no or very mild IMNCT, which is often asymptomatic or unnoticed, and which patients can accommodate without surgery unless, perhaps, they are experiencing notable unhelpful thinking and feelings of distress regarding the symptoms [1,3,7,8,17,18]. Third, we used unweighted items of the CTS-6.…”
Section: Limitationsmentioning
confidence: 99%